Effect of coating phosphorus with humic acids and micronutrients on yield of soybean and maize in succession - M.O.T. de Ávila; S.G. Moreira; F.R.D. Lima; G.V. Pimentel; J.R. Macedo; M.R. Nunes; L.B.W. Gomes; E.G. Morais (Journal of Agriculture and Food Research)
The increasing the efficiency of phosphate and micronutrient fertilization in tropical soils should be better studied to close crop yield gaps. The aim of this study was to evaluate the effect of a soluble P source with or without humic acids (HA) and micronutrients (M) on P-availability and maize and soybean yield in Minas Gerais State, Brazil. The crops were grown under a rainfed and no-till cropping system, with maize grown in the 2016/2017 rainy summer season, wheat grown as a cover crop in the 2017 winter season, and soybean grown in the 2017/2018 crop year. The field trial was organized in a 4 × 2 factorial arrangement [4 sources of P in combination with 2 forms of M supply]. The coated monoammonium phosphate (MAP) P source was supplied in three ways: 1) MAP, 2) MAP + HA, and 3) MAP + HA + M (B, Cu, Mn, and Zn), plus a control for P (no P). The micronutrient supply was 1) Mn + Zn + Cu + B (MZCB) and 2) control for MZCB (no M supply). Coating MAP with HA increased soil P availability but did not increase P content within the soybean leaves. The multivariate approach also showed that soybean yield can increase in response to coating MAP with HA. The study showed that MAP + HA increased soil P content. However, this increase was diminished when micronutrients were included in the same granule (MAP + HA + M). However, P sources raised P in soybean leaves equally compared to control for P. Soybean yield was unaffected by the P source, likely due to adequate leaf P concentrations across all treatments. However, soybean yield generally increased with micronutrient supply. For maize, yields were unaffected by supplying micronutrients with the P source. Conversely, maize yields typically decreased with micronutrient supply, except when using the MAP + HA + M combination granule.